Entre laços de verso: letterings transgeracionais da música brasileira - Silva, Jonathan Teixeira da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The work consists of producing 5 letterings based on meetings between black musicians from the new and old guard of Brazilian music. Unfolding into a book that talks a little about the history of these artists, their encounters and sharing the process of creating each lettering.

O trabalho consiste na produção de 5 letterings baseados em encontros entre musicistas pretos da nova e da velha guarda da música brasileira. Se desdobrando em um livro que fala um pouco sobre a história desses artistas, de seus encontros e compartilhando o processo de criação de cada lettering.
Between verse loops: transgenerational letterings of Brazilian music
Keywords: Música; Música brasileira; Desenho de letras; Letterings; Music; Brazilian music; Lettering design